Praktik Affiliate Marketing Pada Aplikasi Tiktok Shop Perspektif Fatwa DSN-MUI No.151/DSN-MUI/VI/2022 - Luthfi, Hafiz; Muhajir; Fathudin (Kartika: Jurnal Studi Keislaman, 2026)
Affiliate marketing practices on TikTok Shop have grown rapidly as a social media–based digital marketing strategy. In this system, affiliates promote merchants’ products through digital content and earn commissions from successful transactions. Despite its economic benefits, this practice raises issues within Islamic economic law, particularly regarding the determination of the appropriate contractual framework (akad). This study aims to analyze the conformity of affiliate marketing practices on TikTok Shop with the principles of samsarah (brokerage) and wakalah bil ujrah (agency with fee) as regulated in Fatwa No.151/DSN-MUI/VI/2022 issued by the Dewan Syariah Nasional Majelis Ulama Indonesia. This research employs a qualitative approach using a case study method. Primary data were obtained through non-participant observation of affiliate activities, including promotional content, affiliate links, commission schemes, and program policies within the application. Secondary data were derived from DSN-MUI fatwas, classical fiqh literature, and previous studies. The findings indicate that affiliate marketing constitutes a hybrid contract combining samsarah and wakalah bil ujrah. However, clearer role representation is necessary to ensure alignment with Islamic principles of justice, transparency, and trustworthiness